Manajemen Audit Mutu Internal Berstandar ISO 9001: 2015 Dalam Peningkatan Kinerja Sekolah Di SMK Negeri 2 Purwodadi - Eka Wulandari; Nurkolis Nurkolis; Rosalina Br. Ginting (Cetta: Jurnal Ilmu Pendidikan, 2026)
This research is motivated by the importance of managing internal quality audits based on ISO 9001:2015 as an effort to improve school performance. The research aims to analyze internal quality audit management at SMK Negeri 2 Purwodadi. The research uses a qualitative approach with a case study design, through interview techniques, observation and documentation studies involving school principals, quality management teams, internal auditors and teachers. Data analysis was carried out through data reduction, data presentation, and drawing conclusions by testing validity through triangulation of sources and techniques. The research results show that internal quality audit management is carried out systematically through the planning, implementation, reporting and audit follow-up stages in accordance with ISO 9001:2015 principles. The implementation of internal quality audits has an impact on increasing administrative discipline, the effectiveness of learning management, consistent implementation of quality standards, and the development of a culture of continuous improvement. These findings imply that internal quality audits are an important instrument in quality control and continuous improvement of school performance.